FACTORING-BASED BEST NETWORK LAYOUT IDENTIFICATION WITH APPLICATION TO RELIABILITY-CONSTRAINED COST MINIMIZATION PROBLEM - Xiao, Xiao; Takahashi, Natsumi; Enomoto, Daichi; Yamamoto, Hisashi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
In network system design, it becomes more and more difficult to find the best network layout due to rapidly enhanced complexity. Because edges are costly and budget is limited, the number of edges to connect target nodes is restrict to a narrow range, with the number of target nodes is given. Considering such a network system design problem that the number of nodes is given and the number of edges is fixed to a certain value, this paper identifies the best network layout based on factoring theory. We firstly propose three propositions to logically classify network layouts into different types, and then compare the reliabilities of all types via factoring to identify the best network layout, which possesses the greatest reliability. Our best network layout identification approach is applicable to the reliability-constrained cost minimization problem, and is expected to be very conducive to the efficiency improvement of the optimization problem.